Comparison of drug-coated balloon angioplasty versus uncoated balloon angioplasty in treatment of total occlusions with severe femoropopliteal lesions: An additional analysis from the AcoArt I study. (June 2021) - Sun, Guoyi; Liu, Jie; Jia, Senhao; Zhang, Jiwei; Zhuang, Baixi; Jia, Xin; Fu, Weiguo; Wu, Danming; Wang, Feng; Zhao, Yu; Guo, Pingfan; Bi, Wei; et al.
Objectives: Femoropopliteal chronic total occlusions are challenging to treat, and evidence of the effectiveness of drug-coated balloon angioplasty for long femoropopliteal chronic total occlusion lesions is limited. We compared the midterm outcomes of drug-coated balloon angioplasty versus plain old balloon angioplasty (POBA) for femoropopliteal chronic total occlusions. Methods: In total, 95 patients from the AcoArt I trial (ClinicalTrials.gov identifier NCT01850056) with ≥5-cm femoropopliteal chronic total occlusion lesions were enrolled in this post-hoc subset analysis (drug-coated balloon, n  = 50; POBA, n  = 45). The primary endpoints were primary patency and clinically driven target lesion revascularization (CD-TLR) at 24 months. The secondary endpoints were late lumen loss at six months and binary restenosis, major adverse events (composite of death and target limb amputation), change in the Rutherford class, and the ankle-brachial index at 24 months. Results: Demographic, clinical, and lesion characteristics were matched (mean lesion length, 20 cm). The six-month late-lumen loss rate was lower in the drug-coated balloon than POBA group (0.18 ± 0.81 vs. 1.34 ± 0.94 mm, respectively; P  < 0.001). The 24-month primary patency rate was significantly higher in the drug-coated balloon than POBA group (53.85% vs. 17.50%, respectively; P  < 0.001). The CD-TLR rate in the drug-coated balloon and POBA groups was 12.77 and 45.24%, respectively ( P  = 0.002). The 24-month overall mortality rate in the drug-coated balloon and POBA groups was 12.77% and 6.98%, respectively ( P  = 0.360), with no device- or procedure-related deaths. One major amputation had occurred in each group by the 24-month follow-up. Conclusion: The paclitaxel drug-coated balloon shows better primary patency and freedom from target lesion revascularization than POBA at 24month after treatment of femoropopliteal chronic total occlusions (≥5 cm) lesion.